Personalized RNA mutanome vaccines mobilize poly-specific therapeutic immunity against cancer - Sahin, Ugur; Derhovanessian, Evelyna; Miller, Matthias; Kloke, Björn-Philipp; Simon, Petra; Löwer, Martin; Bukur, Valesca; Tadmor, Arbel D.; Luxemburger, Ulrich; Schrörs, Barbara; Omokoko, Tana; Vormehr, Mathias; et al. (Nature (London), 2017)
The authors report the first-in-human application of personalized neo-antigen RNA vaccines in patients with melanoma. Personalized cancer vaccine trials Neoantigens have long been considered optimal targets for anti-tumour vaccines, and recent mutation coding and prediction techniques have aimed to streamline their identification and selection. Two papers in this issue report results from personalized neoantigen vaccine trials in patients with cancer. Catherine Wu and colleagues report the results of a phase I trial of a personalized cancer vaccine that targets up to 20 patient neoantigens. The vaccine was safe and induced tumour-antigen-specific immune responses. Four out of six patients treated showed no recurrence at 25 months, and progressing patients responded to further therapy with checkpoint inhibitor. Ugur Sahin and colleagues report the first-in-human application of a personalized neoantigen vaccine in patients with melanoma. Their vaccination strategy includes sequencing and computational identification of neoantigens from patients, and design and manufacture of a poly-antigen RNA vaccine for treatment. In 13 patients, the vaccine boosted immunity against some of the selected tumour antigens from the individual patients, and two patients showed infiltration of tumour-reactive T cells. These results suggest that personalized vaccines could be refined and tailored to provide clinical benefit as cancer immunotherapies. T cells directed against mutant neo-epitopes drive cancer immunity. However, spontaneous immune recognition of mutations is inefficient. We recently introduced the concept of individualized mutanome vaccines and implemented an RNA-based poly-neo-epitope approach to mobilize immunity against a spectrum of cancer mutations 1 , 2 . Here we report the first-in-human application of this concept in melanoma. We set up a process comprising comprehensive identification of individual mutations, computational prediction of neo-epitopes, and design and manufacturing of a vaccine unique for each patient. All patients developed T cell responses against multiple vaccine neo-epitopes at up to high single-digit percentages. Vaccine-induced T cell infiltration and neo-epitope-specific killing of autologous tumour cells were shown in post-vaccination resected metastases from two patients. The cumulative rate of metastatic events was highly significantly reduced after the start of vaccination, resulting in a sustained progression-free survival. Two of the five patients with metastatic disease experienced vaccine-related objective responses. One of these patients had a late relapse owing to outgrowth of β2-microglobulin-deficient melanoma cells as an acquired resistance mechanism. A third patient developed a complete response to vaccination in combination with PD-1 blockade therapy. Our study demonstrates that individual mutations can be exploited, thereby opening a path to personalized immunotherapy for patients with cancer.